Is External Carotid Artery Hemodynamics Helpful in Detecting Internal Carotid Artery Stenosis?. Issue 1 (March 2023) - Zakko, Jason; Shah, Kejal; Best, Cameron; Baetz, Laureen; Haurani, Mounir J.; Satiani, Bhagwan
Introduction: There is a paucity of validated external carotid artery (ECA) velocity criteria and data on the association between ECA velocities and internal carotid artery (ICA) stenosis by carotid duplex ultrasound (CDU) scanning. Our objectives were to determine the relationships between ECA peak systolic velocity (PSV) and percent stenosis seen on confirmatory imaging, as well as to correlate ECA hemodynamics with known ICA disease by CDU. Methods: A retrospective chart review was performed for patients who had CDU, as well as confirmatory testing such as angiography, at a single academic medical center. ICA stenosis was grouped into 4 categories (0 = <50%, 1 = 50%-69%, 2 = 70%-99%, 3 = 100%) based on validated CDU criteria. ECA PSVs were analyzed, in addition to degree of both ECA and ICA stenosis from the same CDU study. Results: Of 247 carotid arteries reviewed, 136 vessels were included in the final analysis. The mean PSV of the normal ECA cohort (<50% ECA stenosis per the NASCET measurement method) was 135.3 ± 82.1 cm/s, and the mean PSV of the diseased ECA cohort was 279.7 ± 112.2 cm/s. Mean ECA PSV for each category of ICA stenosis was: ICA category 0 = 119.9 cm/s; category 1 = 200.4 cm/s; category 2 = 167.7 cm/s; and category 3 = 155.5 cm/s. There was a statistically significant but non-linear difference in ECA velocities between ICA stenosis categories 0 vs 1 (mean rank diff. −49.91 cm/s; P = .0007); and 0 vs 2 (mean rank diff. −32.61 cm/s; P = .0047). Conclusion: We have demonstrated a possible separation of <50% vs ≥50% stenosis of the ICA using ECA PSV. Although the data suggest a weak but statistically significant correlation between ECA PSV and degree of ICA stenosis, further data with a larger sample size and confirmatory studies are needed to utilize ECA hemodynamics to indicate ICA disease.